Voluntary Wheel Running Reduces Vesicle Development in an Endometriosis Animal Model Through Modulation of Immune Parameters - Appleyard, Caroline B.; Cruz, Myrella L.; Velazquez-Cruz, Johnathan; Rivera-Mendez, Raquel M.; Jimenez-Garcia, Juan G.; Rivera, Luis A.; Mendez-Casillas, Maria del Mar; Flores, Idhaliz; Al-Nakkash, Layla; Chompre, Gladys (Frontiers in Reproductive Health, 2022)
Endometriosis is a chronic gynecological disorder characterized by the growth of endometrial glands and stroma outside the endometrial cavity producing inflammation and pain. Previously we demonstrated that modulation of the hypothalamic pituitary adrenal (HPA) axis exacerbates the development and severity of this condition. A physically active lifestyle has been shown to confer health benefits in many chronic conditions by potentially acting as a stress buffer, thus we hypothesized that voluntary physical exercise can ‘realign/reset’ the HPA axis resulting in reduced endometriosis symptoms in an animal model. Methods: Endometriosis was induced in female Sprague Dawley rats by implanting uterine tissue next to the intestinal mesentery on day 0. Sham controls received sutures only. One group of endometriosis animals had access to a running wheel for 2 weeks prior to endometriosis induction until time of sacrifice at day 60. Sham and endometriosis controls received no exercise. All animals were examined for developed vesicles which were collected and measured. Uterine tissue was analyzed for cellular infiltration. Brain, liver, spleen, adrenal glands, leg muscles and fat were collected, along with peritoneal fluid and blood. Results: Endometriosis animals developed vesicles in 86.96% of the implants with significantly increased mesenteric fat compared to sham (p<0.05). Exposure to exercise significantly decreased the size (p<0.01) and number (p<0.05) of vesicles that developed, as well as the mesenteric fat (p<0.01). Exercised animals had higher levels of lactoferrin in peritoneal fluid, and decreased serum fractalkine and leptin. Exercise significantly increased estrogen alpha receptor expression levels (p<0.01), while significantly decreasing estrogen receptor beta expression (p<0.01) and macrophage infiltration (p<0.05) in vesicles compared to non- exercised animals. Conclusions: Our results suggest that voluntary physical activity might protect against endometriosis and alleviate the associated inflammation via immune modulation of the HPA axis. This offers the potential for further exploration of exercise as a complementary therapy in endometriosis patients.